Effect of testing methods on the bond strength of resin to zirconia-alumina ceramic: microtensile versus shear test - Valandro, Luiz F.; Ozcan, Mutlu; Amaral, Regina [UNESP]; Vanderlei, Aleska [UNESP]; Bottino, Marco A. [UNESP] (Japanese Soc Dental Materials Devices, 2008)
This study tested the bond strength of a resin cement to a glass-infiltrated zirconia-alumina ceramic after three conditioning methods and using two test methods (shear-SBS versus microtensile-MTBS). Ceramic blocks for MTBS and ceramic disks for SBS were fabricated. Three surface conditioning (SC) methods were evaluated: (1) 110-mu m Al(2)O(3)+Silanization; (2) Chairside silica coating+silanization: (3) Laboratory silica coating+silanization. Following surface conditioning, the resin cement (Panavia F) was bonded to the conditioned ceramics. Although no statistically significant differences (p=0.1076) were seen between the test methods, results yielded with the different surface conditioning methods showed statistically significant differences (p<0.0001) (SC2=SC3>SC1.). As for the interaction between the factors, two-way ANOVA showed that it was not statistically significant (p=0.1443). MTBS test resulted in predominantly mixed failure (85%), but SBS test resulted in exclusively adhesive failure. on the effects of different surface conditioning methods, chairside and laboratory tribochemical silica coating followed by silanization showed higher bond strength results compared to those of aluminum oxide abrasion and silanization, independent of the test method employed.
Keywords: Microtensile test; Shear test; Zirconia